A Retrospective Analysis of the Characteristics and Clinical Outcomes of Dental Implants Placed in Romanian Patients - Bogdan Gabriel Sandu; Raluca Iulia Juncar; Abel Emanuel Moca; Paul Andrei Țenț; Mihai Juncar (International Journal of Clinical Practice)
This study aimed to assess the favorable or unfavorable progress of dental implants in a patient sample from Oradea, Romania, considering different variables. A secondary objective was to describe the characteristics of the study sample, as well as different aspects regarding the implants used. This retrospective study analyzed medical records from 1 January 2018, to 1 January 2022, of patients at a dental clinic in Oradea, Romania, who received at least one dental implant. Variables examined included gender, age, systemic diseases, implant location, implant type, and timing of insertion. Clinical and radiological evaluations, using CBCT immediately postplacement and at six months, assessed implant stability and absence of complications. A standardized three-month loading time postinsertion was followed. Exclusion criteria included lack of follow-up, implants placed elsewhere, or incomplete medical records. Quantitative variables were assessed using the Shapiro–Wilk test and nonparametric tests (Mann–Whitney U and Kruskal–Wallis H tests). Fisher’s Exact test analyzed qualitative variables, with Z-tests and Dunn–Bonferroni tests providing detailed results. The study included 344 implants, with 153 (44.5%) placed in female patients and 191 (55.5%) in male patients. Most implants were bone level (61.6%, n = 212) and had a delayed placement (82.6%, n = 284). The majority were situated in the upper posterior dental arch (39.2%, n = 135). Notably, 96.5% (n = 332) of the implants exhibited a positive outcome, irrespective of age, gender, or associated systemic diseases. Immediate postextraction implants displayed a significantly higher association with a negative outcome (41.7% vs. 16.6%), whereas delayed placements were more frequently linked with a positive outcome (83.4% vs. 58.3%) (p=0.040). Employing established techniques and protocols for dental implant insertion led to consistently positive outcomes, irrespective of the implant type, insertion timing, or location. Patient’s age, gender, and associated diseases did not significantly impact implant outcome, highlighting the robustness of these methods in achieving favorable results.